Hubungan Pengetahuan Ibu Hamil Tentang Senam Hamil Degnan Keaktifan Senam Hamil Di Puskesmas Siman Kecamatan Siman Kabupaten Ponorogo. - Sumini Sumini (Akbid Harapan Mulya Ponorogo, 2018)
The maternal mortality rate (MMR) in Kabuaten Ponorogo in 2013 the maternal mortality rate 102 / 100,000 KH ie 10 people, and in 2014 the maternal mortality rate 127 / 100,000 KH ie 12 people. Based on data from sub-district Puskesmas Siman Siman Ponorogo in getting the data AKI in 2013 that there were mother died after childbirth caused bleeding and eclampsia are 2, 1 in 2014 and 1 in 2015. And the women who experienced pain and pingang discomfort during pregnancy are five pregnant women in 2014, four pregnant women in 2015. The purpose of this study was to determine penetahuan pregnant women about pregnancy exercise in pregnancy exercise activeness in Puskesmas Subdistrict Siman Siman Ponorogo. This type of research is quantitative. The population of this research is all pregnant women UK for more than 22 weeks in Puskesmas Siman District of Siman Ponorogo were 23 mothers understood sempel of this study were pregnant women UK for more than 22 weeks in Puskesmas Siman district Siman Regency Ponorogo which follows pregnancy exercise were 23 mothers pregnant, the study did in November 2016. Using sampling technique total sampling. This study uses a variable Idependen ie knowledge and Dependent liveliness. The instrument of knowledge using questionnaires and the activity using the list of attendees. statistical test Chi Square, p <0.05. Editing using data processing, coding, scoring, tabulating. From the results of research in getting nearly half of the respondents are knowledgeable both 10 respondents (43.5%), and nearly all respondents actively following pregnancy exercise 18 respondents (78.3%), based on data on the calculation results of the calculation of statistical test Chi Square p = 0.112 by 0.05 significantly, so Ho accepted or H1 ditolak.yang means there is no relationship of knowledge of pregnant women about pregnancy exercise in pregnancy exercise activeness in Puskesmas Subdistrict Siman Siman Ponorogo. Pregnant women expected more increases knowledge about pregnancy exercise in order to further enhance the liveliness of pregnancy exercise. In the hope of health workers and cadres capable of giving information to the public about pregnancy exercise.